THE EFFECTIVENESS OF HONEY GIVING AGAINST DYMENORRHEA IN ADOLESCENT OF WOMEN YOUTH ORGANIZATION ( KARANG TARUNA) AT ANDAMUI VILLAGE, CIWARU, KUNINGAN REGENCY , WEST JAVA - RISNA APRIYANI; RISZA CHOIRUNISSA; RETNO WIDOWATI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Menstruation is periodic vaginal bleeding due to the shedding of the endometrial lining of the uterus, menstrual periods are normal for women every month, some women who experience menstruation usually have cramps, and there will be pain that can stop daily activities during menstruation or what is called dysmenorrhea. Dysmenorrhea can be treated with pharmacological therapy NSAIDs, and non-pharmacological one of them with the consumption of honey. This study to determine the effectiveness of giving honey to dysmenorrhea in adolescent coral cadets Andamui village ciwaru district Kuningan district west java. Quasi-experiment research with one group pretest-posttest design without control group. In this study researchers only intervened in one group. The sample in this study amounted to 17 adolescent aged 15-20 years. The sampling technique used purposive sampling that met the inclusion and exclusion criteria. The research instrument used a Numeric Rating Scale (NRS) pain measuring instrument questionnaire. The results of the Wilcoxon statistical test showed that there was an effect of giving acacia crassicarpa honey to the decrease in the level of pain in dysmenorrhea with a significancy value of Asymp Sig (2tailed) = 0.000 (α < 0.05). The results of this study showed that there was a decrease in the level of pain after giving acacia crassicarpa honey. There is a significant effect on giving honey to reduce dysmenorrhea pain.